Clinical effectiveness of the START (STrAtegies for RelaTives) psychological intervention for family carers and the effects on the cost of care for people with dementia: 6-year follow-up of a randomised controlled trial. (January 2020) - Livingston, Gill; Manela, Monica; O'Keeffe, Aidan; Rapaport, Penny; Cooper, Claudia; Knapp, Martin; King, Derek; Romeo, Renee; Walker, Zuzana; Hoe, Juanita; Mummery, Cath; Barber, Julie
Abstract : Background: The START (STrAtegies for RelaTives) intervention reduced depressive and anxiety symptoms of family carers of relatives with dementia at home over 2 years and was cost-effective. Aims: To assess the clinical effectiveness over 6 years and the impact on costs and care home admission. Method: We conducted a randomised, parallel group, superiority trial recruiting from 4 November 2009 to 8 June 2011 with 6-year follow-up (trial registration: ISCTRN 70017938). A total of 260 self-identified family carers of people with dementia were randomised 2:1 to START, an eight-session manual-based coping intervention delivered by supervised psychology graduates, or to treatment as usual (TAU). The primary outcome was affective symptoms (Hospital Anxiety and Depression Scale, total score (HADS-T)). Secondary outcomes included patient and carer service costs and care home admission. Results: In total, 222 (85.4%) of 173 carers randomised to START and 87 to TAU were included in the 6-year clinical efficacy analysis. Over 72 months, compared with TAU, the intervention group had improved scores on HADS-T (adjusted mean difference −2.00 points, 95% CI −3.38 to −0.63). Patient-related costs (START versus TAU, respectively: median £5759 v. £16 964 in the final year; P = 0.07) and carer-related costs (median £377 v. £274 in the final year) were not significantly different between groups nor were group differences in time until care home (intensity ratio START:TAU was 0.88, 95% CI 0.58–1.35). Conclusions: START is clinically effective and this effect lasts for 6 years without increasing costs. This is the first intervention with such a long-term clinical and possible economic benefit and has potential to make a difference to individual carers. Declarations of interest: G.L., Z.W. and C.C. are supported by the UCLH National Institute for Health Research (NIHR) Biomedical Research Centre. G.L. and P.R. were in part supported by the National Institute for Health Research (NIHR) Collaboration for Leadership in Applied Health Research and Care (CLAHRC) North Thames at Bart's Health NHS Trust. The views expressed are those of the author(s) and not necessarily those of the NHS, the NIHR or the Department of Health. Z.W. reports during the conduct of the study; personal fees from GE Healthcare, grants from GE Healthcare, grants from Lundbeck, other from GE Healthcare, outside the submitted work.